PENGARUH PERHATIAN GURU DAN ORANG TUA PADA MAKANAN SEHAT YANG DIKONSUMSI PESERTA DIDIK TERHADAP TUMBUH KEMBANG PESERTA DIDIK DALAM PANDANGAN ISLAM DI SD NEGERI 067952 PANGKALAN MANSYUR KOTA MEDAN - SYAFRIL . (JURNAL ILMIAH KOHESI, 2019)
This study aims to determine whether there is an influence of the attention of teachers and parents on healthy food consumed by students towards the growth and development of students in Islamic view at SD Negeri 067952, Mansyur Base, Medan City. The subjects in this study were students of Public Elementary School 067952 Pangkalan Mansyur Kota Medan from class I to class VI with a sample of 86 students. Data collection methods in this study used questionnaires, interviews, observations and documentation to find out the teacher's attention to the healthy foods consumed by students, the parents 'attention to healthy foods consumed by students and the students' growth and development variables. Data analysis techniques in this study used the computer program spss. 23 for windows.The results showed that the variable teacher's attention to healthy food consumed by students (X1) in the good category at intervals of 40-45 there were 50 respondents with a percentage of 59.5%, in the sufficient category at intervals of 34-39 there were 29 respondents with a percentage of 34, 6%, and in the less category at 28-33 intervals there were 5 respondents with a percentage of 6%. Variables of parents' attention to healthy food consumed by students (X2) in the good category at intervals of 42.3-45 there were 49 respondents with a percentage of 58.4%, in the sufficient category at intervals 38, 3-41.7 there were 32 respondents with percentage of 38.1%, and in the less category at intervals of 35-37.7 there were 3 respondents with a percentage of 3.6%. Student growth and development variables (Y) in either category at 41.7-45 intervals there were 59 respondents with a percentage of 70.2%, in the sufficient category at 36.7-40.3 intervals there were 20 respondents with a percentage of 23.9%, and in the less category at an interval of 30-35.3 there were 5 respondents with a percentage of 6%.There is a significant influence between the variable teacher's attention on healthy food consumed by students (X1) and the variable parents' attention to healthy food consumed by students (X2) on the growth and development of students (Y) at SD Negeri 067952 Pangkalan Mansyur, Medan. This is evidenced by the results of calculating the correlation that obtained r count 0.484 and greater than r table 0.212 with a significant level of 5%.